On numerals in Georgian Sign language (GESL) - Makharoblidze, Tamar ("Intercultural Dialogues" Transactions, 2023)
Georgian sign language (GESL) is a language of Deaf and Hard of Hearing (DHH) people in Georgia. There are about 2 500 DHH in the country. They are bilinguals – having two native languages: GESL and spoken Georgian. Thus, they expect to have the bilingual education in schools. Numerals in all languages are morphological denoting the number, order or part. Accordingly, numerals can be cardinal, ordinal or fractional/distributive. GESL repeats the universal approach of languages ​​to number. Almost all sign languages ​​use expected combinations of fingers to represent a number, and it concerns to cardinal numerals. Sign languages ​​have pentagram systems, a number is transmitted with the fingers of the hand and this is the most convenient system, while many spoken languages use decimal system or system of twenty – as spoken Georgian. Actually, in spoken languages the four most common number system types are: Decimal number system (Base 10) Binary number system (Base 2) Octal number system (Base 8) Hexadecimal number system (Base 16) This difference between the counting systems of spoken Georgian and GESL must be carefully taken into account while teaching cardinal numerals to Deaf children in Georgia. In general, sign languages ​​are not characterized by a system of marking affixes of segmental morphology, although the separation of morphemes and derivational affixes still occur in some sign languages. GESL shows a special system in this respect. Ordinal numerals are produced by adding an ordinal sign, and this is a derivational suffix, which is a completely delexicalized affix. Interestingly, GESL shows the numeral incorporation as well. It is important that GESL has proper morpho-lexical means to convey the system of numerals.